Could cone-beam computed tomography demonstrate the lateral accessory canals? - Yan Ji; Shanhui Wen; Shu Liu; Min Zhu; Menghuan Yao; Tiemei Wang; Zitong Lin (BMC, 2017)
Abstract Background Recently, using cone-beam computed tomography (CBCT) to assess root canal morphology has become popular; however, few studies have examined its efficiency to assess the entire root canals, including the tiny lateral and accessory canals (LACs). This study aimed to assess the ability of CBCT to evaluate the root canal of mandibular incisors at three different scanning settings, compared with the canal staining and tooth clearing (CS) technique as the gold standard. Methods CBCT images of 70 extracted mandibular incisors were taken using NewTom VG CBCT at high-resolution scan mode (HZ), zoom scan mode (ZS), and full scan mode (FS), with different scanning settings. A radiologist, a postgraduate student, and an endodontist assessed the root canal morphology in a blinded manner. The number of root canals (NC), canal configuration according to Vertucci's classification (VC), and LACs were evaluated twice by each evaluator using the CBCT images, in comparison with CS. Comparisons of the differences were used the chi-square test, and the intra-evaluator and inter-evaluator agreement were used the Kappa statistics; the significance level was set at 0.05. Results The voxel dimension of HZ, ZS and FS modes were 0.125 mm, 0.20 mm and 0.25 mm respectively, and the HZ mode had significant increased scanning doses. For NC, the diagnostic accuracy was >90% in all three modes, with no significant difference among the evaluators and modes. VC and LAC could only be evaluated in HZ mode. For VC, the accuracies were 97.1%, 94.3%, and 92.9% respectively, with no significant differences among the three evaluators. For LAC, the accuracies were 80.0%, 13.3%, and 33.3% respectively, and there were significant differences among the three evaluators. Intra-evaluator agreement was excellent, with the kappa values indicating "perfect" to "substantial" agreement. Inter-evaluator agreement was excellent for NC and VC; however, Kappa values could not be analyzed due to LACs detected were so variable. Conclusions As far as possible, the HZ mode should be chosen to demonstrate the root canal system, and partial LACs could be detected using this mode; however, the potential benefit of the diagnostic information must be weighed against the increased radiation dose.